Comparative proteomics and metallomics studies in Arabidopsis thaliana leaf tissues: Evaluation of the selenium addition in transgenic and nontransgenic plants using two‐dimensional difference gel electrophoresis and laser ablation imaging. Issue 7 (April 2014) - Maciel, Bruna C. M.; Barbosa, Herbert S.; Pessôa, Gustavo S.; Salazar, Marcela M.; Pereira, Gonçalo A. G.; Gonçalves, Danieli C.; Ramos, Carlos H. I.; Arruda, Marco A. Z.; Lodeiro, Carlos; Martínez, José Luis Capelo; Santos, Hugo M.
<x xml:space="preserve">Abstract</x> The main goal of this work is to evaluate some differential protein species in transgenic (T) and nontransgenic (NT) Arabidopsis thaliana plants after their cultivation in the presence or absence of sodium selenite. The transgenic line was obtained through insertion of CaMV 35S controlling nptII gene. Comparative proteomics through 2D‐DIGE is carried out in four different groups (NT × T; NT × Se‐NT (where Se is selenium); Se‐NT × Se‐T, and T × Se‐T). Although no differential proteins are achieved in the T × Se‐T group, for the others, 68 differential proteins (by applying a regulation factor ≥1.5) are achieved, and 27 of them accurately characterized by ESI‐MS/MS. These proteins are classified into metabolism, energy, signal transduction, disease/defense categories, and some of them are involved in the glycolysis pathway—Photosystems I and II and ROS combat. Additionally, laser ablation imaging is used for evaluating the Se and sulfur distribution in leaves of different groups, corroborating some results obtained and related to proteins involved in the glycolysis pathway. From these results, it is possible to conclude that the genetic modification also confers to the plant resistance to oxidative stress.